1999
DOI: 10.1021/ma990528s
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Linking Polymerization in Two-Dimensional Assemblies:  Effect of the Reactive Group Site

Abstract: The cross-linking polymerization of hydrated amphiphiles in monolayers, bilayers, and nonlamellar phases, i.e., bicontinuous cubic and the inverted hexagonal phases, is an effective method to modify their properties. Polymerization of monomeric amphiphiles in an assembly proceeds in a linear or cross-linking manner depending on the number and location of polymerizable groups per monomer. Polymerization of hydrated lipids with reactive groups in each hydrophobic tail yields cross-linked polymers. Sisson et al. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 27 publications
5
47
0
1
Order By: Relevance
“…Although cross-linked PSLBs are formed by both methods, previous studies on poly(bis-SorbPC) vesicles have shown that redox initiation produces a greater degree of polymerization (X n = 50-500) than UV irradiation (X n = 3-10). [32][33][34] A similar trend likely occurs in bis-SorbPC PSLBs polymerized by these two methods, and significant differences in their respective structural properties have been observed. 14,15 The origin of these differences may be different propagation mechanisms for the two methods.…”
Section: Xps Of Uv-and Redox-polymerized Bis-sorbpc Bilayerssupporting
confidence: 52%
“…Although cross-linked PSLBs are formed by both methods, previous studies on poly(bis-SorbPC) vesicles have shown that redox initiation produces a greater degree of polymerization (X n = 50-500) than UV irradiation (X n = 3-10). [32][33][34] A similar trend likely occurs in bis-SorbPC PSLBs polymerized by these two methods, and significant differences in their respective structural properties have been observed. 14,15 The origin of these differences may be different propagation mechanisms for the two methods.…”
Section: Xps Of Uv-and Redox-polymerized Bis-sorbpc Bilayerssupporting
confidence: 52%
“…Previous studies demonstrated that cross-linked lipid vesicles were stable in the presence of excess surfactant, whereas unpolymerized or linearly polymerized vesicles were dissolved by surfactant. 7,21 Further studies also showed that the surfactant solubilization was dependent on the degree of polymerization, extent of cross-linking, and location of the reactive groups in the lipid. Vesicles composed of oligomers were efficiently dissolved with TX-100, while vesicles composed of longer linear polymeric lipids were less readily solubilized.…”
Section: Resultsmentioning
confidence: 99%
“…Monomer 2c can form a Q II phase without co-monomers and is intrinsically cross-linkable, but the doubly-reactive single tail is synthetically complex to produce. 25 These papers, as well as other papers by O'Brien and co-workers on these polymerizable Q II -phase systems, [28][29][30][31] focused mostly on fundamental studies of chainaddition polymerization in Q phases. They also studied the diffusion of dendrimers in the water channels of the cross-linked Q II -phase mixed-lipid systems and found that it was sufficiently rapid for the materials to be potentially useful for controlled release applications of encapsulated large drugs and macromolecules.…”
Section: Nanoporous Polymer Materials Via the Direct Polymerization Omentioning
confidence: 99%